Michael Psellos’ ‘Arrangement’ of Hermias’ Commentary on Plato’s Phaedrus - Arabatzis, Georges (Peitho. Examina Antiqua, 2010)
The Byzantine philosopher Michael Psellos (11th century) wrote a brief treatise entitled An Explanation of the Drive of the Soul Chariot and the Army of Gods According to Plato in the Phaedrus. The treatise consists of a compilation of excerpts from Hermias’ commentary on the Phaedrus. Psellos does not mention Hermias’ name but rather traces the origins of the treatise back to some “Greek theologians”. Psellos’ text presents a great interpretative challenge: the order of the myths about the charioteer and the parade of gods is reversed so that the former explicates the latter in such a way that the whole Platonic argument is dismissed as “absurd”. The Phaedrus in the Neo ‑Platonic tradition (in Iamblichus in particular) is considered to be a strictly theological dialogue. Yet, Psellos’ arrangement shows that he was not interested in the mythographical or allegorical dimension of the excerpts. He rather focused on the epistemic problem, i.e., a reduction of the trichotomy of the soul into a duality of principles. Thus, he followed certain Aristotelian commentators. Psellos suggests a reduction that is subjectivist or individualist in its nature and he refuses to identify individual intellect with any particular piety.